Kepemilikan Manajemen, Kepemilikan Institusional pada Corporate Social Responsibility Disclosure dengan Kinerja Lingkungan sebagai Pemoderasi - Andriani, Ni Putu Melia; Sudana, I Putu (E-Jurnal Akuntansi, 2023)
Corporate Social Responsibility (CSR) is a positive activity carried out by companies to contribute to protecting the environment. The research objective was to obtain empirical evidence of the effect of management ownership and institutional ownership on CSR disclosure with environmental performance as a moderator. The research was conducted on manufacturing companies listed on the IDX in 2018-2020. There were 47 companies used as samples. Research data collection uses documentation techniques, while analysis techniques use Moderated Regression Analysis (MRA). The results of the analysis show that management ownership has no effect on CSR disclosure. Institutional ownership is correlated with CSR disclosure. Environmental performance cannot moderate the effect of management ownership on CSR disclosure. Environmental performance moderates the effect of institutional ownership on CSR disclosure. The implication of this research is that management ownership cannot be used as a reference for companies in making CSR disclosure decisions. Institutional ownership in this study can be used as a guideline and material for consideration when making CSR disclosure decisions . Keywords: Management Ownership; Institutional Ownership; Environmental Performance; Corporate Social Responsibility Disclosure